2018
DOI: 10.1177/1049909118779917
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived End-of-Life Care Competencies of Health-Care Providers at a Large Academic Medical Center

Abstract: Differences in self-perceived EOL care competencies were identified among disciplines, particularly between physicians and nurses. The results provide evidence for assessing health-care providers to identify their specific training needs before implementing educational programs on EOL care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 22 publications
3
58
0
7
Order By: Relevance
“…All of the studies were conducted using a quantitative method; however, a few studies also contained a minor qualitative component. The sample size varied from 90–7,922, and most of the participants were nurses, although two of the studies included other healthcare professionals, with the participation of the nurses reported separately (Lazenby, Ercolano, Schulman‐Green, & McCorkle, ; Montagnini, Smith, Price, Ghosh, & Strodtman, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies were conducted using a quantitative method; however, a few studies also contained a minor qualitative component. The sample size varied from 90–7,922, and most of the participants were nurses, although two of the studies included other healthcare professionals, with the participation of the nurses reported separately (Lazenby, Ercolano, Schulman‐Green, & McCorkle, ; Montagnini, Smith, Price, Ghosh, & Strodtman, ).…”
Section: Resultsmentioning
confidence: 99%
“…The nurse's competence in the identification of the psychosocial needs of the patient included an ability to assess the emotional distress a patient experiences and, second, to recognise and understand the patient's grief and sorrow (Kim et al, ; Autor, Storey, & Ziemba‐Davis, ; Kim & Hwang, ; Iranmanesh et al, ; Price et al, ; Schnell‐Hoehn et al, ). Supporting the patient in coping with a life‐limiting illness meant that the nurse had to have the necessary skills to assist the patient in meeting their social needs, promote communication between family members (Desbiens & Fillion, ; Ly et al, ) and also provide care such that the patient and his or her family are able to identify resources to cope with the distress and bereavement the illness causes (Desbiens & Fillion, ; Ly et al, ; Price et al, ; Montagnini et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations